Urban livelihood strategies and agricultural activities in Khayalitsha communities, Western Cape, South Africa - Perret, S. (Sylvain) (University of Pretoria, 2013)
Thesis (M Inst Agrar (Land-Use Planning))--University of Pretoria, 2006.